Empirical Study Of E-recruitment Technology Adoption In Malaysia: Assessment Of A Modified Technology Acceptance Model - Tong, David Yoon Kin (2007)
E-recruitment has the potential to change some of the 'traditional' recruitment sources. With this continuous growth of job seekers population using this technology for job search, this research aims to analyse and predict jobseekers' perceptions of e-recruitment technology adoption and utilization.